Environmental Conditionality of the Kalmyk Nomadic Economy - Aleksandr Narmaevich Komandzhaev (Tarih Kültür ve Sanat Araştırmaları Dergisi, 2018)
The development of the Kalmyk farming in the late 19th – early 20th centuries is analyzed in the present article. Special attention is paid to the problem of effective management in arid climate and marketization of the region. The article considers the indicators of Kalmyk nomadic farming development, estimates stocking level in the period under review and establishes the impact of market conditions on nomadic farming development. The article employs a wide range of sources and literature. The results demonstrate that the Kalmyk cattle-breeders ran their farms efficiently in arid climate taking market fluctuations into account. That was the indication of sufficient economic efficiency and ecological suitability of that type of economic management in the late 19th – early 20th centuries.